(untitled) (Research, Society and Development, 2021)
Brazil has grown a lot in the beer segment with the big manufacturers and with the craft breweries that appear constantly on the market. However, water use in a brewing industry can be 4 to 10 times greater than the volume of beer produced. In view of the large amount of water needed in beer production, the work aimed to verify whether the use of water in beer production is sustainable, taking as a parameter the price implemented to users and the costs for use. Two assessment methods were adopted, the construction of a production function and the assessment of the willingness to pay for water in production. It was concluded that there is an investment in technologies by the main beer factories for the preservation of natural resources, especially water, and that the propensity to pay for the resource is treated based on the speeches of the representatives as already being done through investments in technologies for greater impact on the environment and reduction of negative externalities.